Communicate from the heart - Razak, Dzulkifli Abd (2010)
THIS is my 16th year writing for the New Straits Times (NST). It started in 1994 to coincide with the establishment of Pusat Racun Negara (National Poison Centre) at Universiti Sains Malaysia (USM). Pusat Racun Negara also doubles as the World Health Organization Collaborating Centre for Drug Information. The former is a first for Malaysia; the latter, a first in Asia.